Reconsidering the rise in A-level mathematics participation - Noyes, Andrew; Adkins, Michael (Oxford University Press, 2016)
There is growing support for making the study of mathematics to age 18 compulsory for all young people in England. This paper aims to inform this debate through new insights into historic A-level Mathematics participation trends. We analyse full-year cohorts from the Department for Education’s National Pupil Database for age-16 students from 2004-2010, a total of just over 4.5 million young people. Using a cohort-tracking approach we aim to better understand the flow of young people through upper secondary mathematics education. Earlier work identified GCSE attainment as the strongest predictor of A-Level Mathematics participation. In this paper we show that the percentage of students progressing to A-Level by GCSE grade has not changed significantly over the period in question, with some exceptions. This implies that the increase in A-level Mathematics numbers is largely explained by the growing proportion of higher GCSE grades. We discuss the implications for policy that this raises, e.g. the possible impact of making GCSE mathematics more demanding.